2020
DOI: 10.1007/s12098-019-03177-y
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm and Lung Ultrasound Indices in Prediction of Outcome of Weaning from Mechanical Ventilation in Pediatric Intensive Care Unit

Abstract: Objective To predict the added value of diaphragmatic and lung ultrasound indices (US) in anticipation of the outcome of mechanical ventilation of pediatric patients in the intensive care unit. Methods This prospective study was conducted in Zagazig University, Pediatric Hospitals, PICU; Egypt. One hundred six mechanically ventilated children aged between 1 mo to 170 mo were included in the study. All patients were candidates for weaning and have been given a chance for spontaneous breathing trial (SBT), durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 18 publications
5
45
2
Order By: Relevance
“…Best cut-off values for DTF, DE and LUS for predicting weaning failure were < 23.17%, < 6.2 mm, and ≥ 12 respectively. But the current study has unusually high extubation failure rate of 39.6% [4].Previous study in 50 children also demonstrated similar cut-off of ≥21% for DTF for successful weaning with successful weaning in 78% children [2]. Recent meta-analysis of 742 adults reported summary AUROC of 0.838 and 0.859 for DTF and DE, respectively [5].…”
supporting
confidence: 50%
See 4 more Smart Citations
“…Best cut-off values for DTF, DE and LUS for predicting weaning failure were < 23.17%, < 6.2 mm, and ≥ 12 respectively. But the current study has unusually high extubation failure rate of 39.6% [4].Previous study in 50 children also demonstrated similar cut-off of ≥21% for DTF for successful weaning with successful weaning in 78% children [2]. Recent meta-analysis of 742 adults reported summary AUROC of 0.838 and 0.859 for DTF and DE, respectively [5].…”
supporting
confidence: 50%
“…Ultrasound can assess percentage change in diaphragmatic thickness from expiration to inspiration (diaphragmatic thickening fraction, DTF) and amplitude of diaphragmatic dome movements in respiratory cycle (diaphragmatic excursion, DE) which are indicators of strength of diaphragmatic contractions [2]. Lung parenchyma is assessed by a semi-quantitative score (Lung Ultrasound Score, LUS) based on frequency of B-lines in different lung fields (score 0 to 3 in each field), with higher score indicating worse parenchymal status [3].In a study published in this issue of the journal by Abdel Rahman DA et al, 106 mechanically ventilated children were examined with diaphragm and lung ultrasound during SBT [4]. They found that infants with weaning failure had significantly lower DTF and DE, and higher LUS compared to successful weaning (p < 0.001 for all comparisons).…”
mentioning
confidence: 99%
See 3 more Smart Citations